(x÷a)-(y÷b)=a+b;(x÷'a'square)+(y÷'b'square)=0 .....then 'y' is
Answers
Answered by
1
x/a-y/b=a+b
x/a^2+y/b^2=0
b^2x+a^2y=0
b^2x= - a^2y
So, x= - a^2y/b^2
Now,x/a-y/b=a+b
bx-ay=a^2b+ab^2
Now put the value of x then we get
b×(-a^2y/b^2)-ay=ab(a+b)
-a^2y/b -ay=ab(a+b)
-ay(a/b+1)=ab(a+b)
-ay(a+b)/b=ab(a+b)
-y=b^2
So,y= -b^2
x/a^2+y/b^2=0
b^2x+a^2y=0
b^2x= - a^2y
So, x= - a^2y/b^2
Now,x/a-y/b=a+b
bx-ay=a^2b+ab^2
Now put the value of x then we get
b×(-a^2y/b^2)-ay=ab(a+b)
-a^2y/b -ay=ab(a+b)
-ay(a/b+1)=ab(a+b)
-ay(a+b)/b=ab(a+b)
-y=b^2
So,y= -b^2
Answered by
0
Answer:
HAPPY CHRISTMAS DEAR
DO YOU REMEMBER ME
Similar questions